2015
DOI: 10.1002/esp.3761
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sheet wash erosion rates in a mountainous semi‐arid basin using environmental radionuclides and a stream power model

Abstract: Erosion rates and processes define how mountainous landscapes evolve. This study determines the range of erosion rates in a semi‐arid landscape over decadal time spans and defines the dominant processes controlling variability in erosion rates. The varying topography and climatic regimes of the Xiying Basin (Qilian Shan Mountains, China) enables us to examine the relative roles of sheet wash versus rainsplash and the influence of vegetation on soil erosion and deposition. Soil erosion rates since 1954 were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 79 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…This index is commonly used to examine the relation between surface processes and vegetation coverage (e.g. Butler and Walsh, 1998;Laymon et al, 1998;McGuire et al, 2014;Geng et al, 2015). The NDVI index consists of the normalized difference between the spectral reflectance of the near-infrared (NIR) spectrum and the visible (VIS) spectrum:…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…This index is commonly used to examine the relation between surface processes and vegetation coverage (e.g. Butler and Walsh, 1998;Laymon et al, 1998;McGuire et al, 2014;Geng et al, 2015). The NDVI index consists of the normalized difference between the spectral reflectance of the near-infrared (NIR) spectrum and the visible (VIS) spectrum:…”
Section: Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…Equation (4) is the 1D version of the stream power equation, which we use following Geng et al (2015), and we apply the twodimensional (2D) versions of Equations (5) and (6). We then used Equations (4)-(6) to compare predictions of net erosion or deposition to our estimates.…”
Section: Hillslope Transport Lawsmentioning
confidence: 99%
“…Geng et al (2015) recently showed a sheet wash model predicted measured erosion better than a diffusive model on planar hillslopes. Geng et al (2015) recently showed a sheet wash model predicted measured erosion better than a diffusive model on planar hillslopes.…”
Section: Relationship Between Local Net Soil Transport and Terrain Atmentioning
confidence: 99%
See 2 more Smart Citations